2000
DOI: 10.1080/096374800750049611
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienols inhibit growth of ZR-75–1 breast cancer cells

Abstract: The vitamin E component of palm oil provides a rich source of tocotrienols which have been shown previously to be growth inhibitory to two human breast cancer cell lines: responsive MCF7 cells and unresponsive MDA-MB-231 cells. Data presented here shows that the tocotrienol-rich fraction (TRF) of palm oil and individual fractions (alpha, gamma and delta) can also inhibit the growth of another responsive human breast cancer cell line, ZR-75-1. At low concentrations in the absence of oestrogen tocotrienols stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Previous reports by Nesaretnam and co-workers [12,13,19-21] have shown that tocotrienol on its own can inhibit growth of human breast cancer cells in vitro [12,19] as well as in athymic nude mice [21]. The combination of tumour lysate pulsed-DC and TRF supplementation observed in this study could inhibit the growth of breast tumour in the mouse model.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Previous reports by Nesaretnam and co-workers [12,13,19-21] have shown that tocotrienol on its own can inhibit growth of human breast cancer cells in vitro [12,19] as well as in athymic nude mice [21]. The combination of tumour lysate pulsed-DC and TRF supplementation observed in this study could inhibit the growth of breast tumour in the mouse model.…”
Section: Discussionsupporting
confidence: 54%
“…Hence, certain nutritional products or supplement may provide a boost for host immune system to fight tumour and this could improve the outcome of treatment. We have previously shown that vitamin E, namely the tocotrienol-rich fraction isolated from palm oil is effective in inhibiting the growth of human mammary cancer cell line in culture [5,12,13]. In this study, investigation on the effects of TRF supplementation, a non-toxic natural compound from palm oil to improve the efficacy of vaccines against breast cancer in our BALB/C mouse model has been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…However, this was not statistically significant ( P = 0.27). Previous studies carried out in our laboratory showed that tocotrienols inhibited growth and proliferation of breast cancer cells [6-8]. Another study reported that the anticarcinogenic property of tocotrienols in synergy with tamoxifen is more potent than tamoxifen alone [11].…”
Section: Discussionmentioning
confidence: 99%
“…Because tocotrienols are more potent than tocopherols [6-8,11,12], we hypothesize that tocotrienol intake may be associated with improved survival and lower recurrence in patients with early breast cancer. We investigated the effectiveness of TRF in combination with tamoxifen compared with placebo with tamoxifen as adjuvant therapy in improving breast cancer-specific survival in women with estrogen receptor (ER)-positive tumors who had been treated for TNM stage 1 and stage 2 (early) breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Other compounds such as fatty acid amides and retinoid × receptor (RXR) agonists are also effective against breast cancer in cell lines and in animal models [2,3]. Interestingly, a macrolide antibiotic-rifampicin, the antimycotic drug clotrimazole, endogenous cannabinoids such as anandamide, RXR agonists (rexinoids) such as targretin, and tocotrienol forms of Vitamin E share the ability to inhibit the growth of various types of cancer [2-8]. Some of these compounds such as rifampicin, targretin, and tocotrienols have also been shown to have synergistic or additive effects against cancer when used together with tamoxifen [4,7,9].…”
Section: Introductionmentioning
confidence: 99%